Practical Recommendations of Scientific Society for the Study of Human Microbiome and Russian Gastroenterological Association (RGA) for Probiotics in Treatment and Prevention of Gastroenterological Diseases in Adults - V. T. Ivashkin; I. V. Mayev; D. I. Abdulganieva; S. A. Alekseenko; N. Yu. Ivashkina; N. V. Korochanskaya; S. N. Mammaev; E. A. Poluektova; A. S. Trukhmanov; Yu. P. Uspensky; V. V. Tsukanov; O. S. Shifrin; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To provide practical recommendations on the use of probiotics for the treatment and prevention of gastroenterological diseases in adults.General provisions. Probiotics are living microorganisms that benefit the health of the host when administered in adequate amounts. The main functions of probiotics include the support for colonisation resistance, the metabolism of food substrates and utilisation of end metabolites, the production of substrates necessary for the macro-organism, as well as the regulation of local and adaptive immune responses. Probiotics can be registered in the Russian Federation as biologically active food additives (BAFA) or as pharmaceutical products (drugs) in accordance with the microbiological standards and legislative requirements of the Russian Federation. The probiotics registered in the Russian Federation as BAFA for adults include bacteria of the Lactobacillus, Bifidobacterium, Enterococcus, Pediococcus, Lactococcus, Streptococcus, Bacillus, and Escherichia genera, and fungi of the Saccharomyces genus; probiotics registered as drugs — bacteria of Lactobid, Lactobacid, Escherichia and Enterococcus genera and fungi of the Saccharomyces genus. Some probiotics registered in the Russian Federation include probiotic strains that have proved to be effective for the prevention and treatment of antibiotic-associated diarrhea, the prevention of C. difficile-associated disease, the eradication of H. pylori infection, as well as for the treatment of irritable bowel syndrome and functional constipation.Conclusions. The clinical efficacy of probiotics depends on the probiotic strains included in their composition and is confirmed by a comparative analysis of the results of appropriate clinical studies. Not all probiotics registered in the Russian Federation as BAFA or drugs contain bacterial or fungal strains; as a result, the expected clinical effect may not be achieved.